Thermophiles; or, the Modern Prometheus: The Importance of Extreme Microorganisms for Understanding and Applying Extracellular Electron Transfer - Lusk, Bradley G. (Frontiers in Microbiology, 2019)
Approximately four billion years ago, the first microorganisms to thrive on earth were anaerobic chemoautotrophic thermophiles, a specific group of extremophiles that survive and operate at temperatures 50 - 125°C and do not use molecular oxygen (O2) for respiration. Instead, these microorganisms performed respiration via dissimilatory metal reduction by transferring their electrons extracellularly to insoluble electron acceptors. Genetic evidence suggests that Gram-positive thermophilic bacteria capable of extracellular electron transfer (EET) are positioned close to the root of the Bacteria kingdom on the tree of life. On the contrary, EET in Gram-negative mesophilic bacteria is a relatively new phenomenon. This suggests that EET evolved separately in Gram-positive thermophiles and Gram-negative mesophiles, and that EET in these distinct bacterial types is a result of a convergent evolutionary process leading to homoplasy. Thus, the study of dissimilatory metal reducing thermophiles provides a glimpse into some of Earth’s earliest forms of respiration. This will provide new insights for understanding biogeochemistry and the development of early Earth in addition to providing unique avenues for exploration and discovery in astrobiology. Lastly, the physiological composition of Gram-positive thermophiles, coupled with the kinetic and thermodynamic consequences of surviving at elevated temperatures, makes them ideal candidates for developing new mathematical models and designing innovative next-generation biotechnologies.